Performance and multipath fading modelling of a line-of-sight microwave link - Hu, Chun Feng. (2008)
Irregular variations in the refractive index structure may cause multipath fading for line-of-sight microwave links. Since very few propagation measurements have been conducted in Southeast Asia previously, there is a need for propagation and radiometeorological measurement data in this area to test and improve the accuracy of existing multipath fading prediction methods.